The influence of hospitalizations due to exacerbations or spontaneous pneumothoraxes on the quality of life, mental function and symptoms of depression and anxiety in patients with COPD or asthma. (April 2014) - Filipowski, Marek; Bozek, Andrzej; Kozlowska, Renata; Czyżewski, Damian; Jarzab, Jerzy
Abstract Background: Patients with bronchial asthma or chronic obstructive pulmonary disease (COPD) frequently have a low quality of life (QoL) in addition to depression symptoms. The aim of this study was to compare the QoL, depression symptoms, mental function and anxiety in patients with asthma or COPD exacerbations or spontaneous pneumothoraxes (SP) to patients with stable disease. Materials and methods: Patients with a confirmed diagnosis of severe (III degree) bronchial asthma or COPD were included in this study. Prospective observations of asthma or COPD exacerbations or SP were performed over a three-year period. QoL was assessed using St. George's Respiratory Questionnaire (SGRQ). In addition, the AQ20 questionnaire (AQ20), the Hospital Anxiety and Depression Scale (HADS) and the Mini-Mental State Examination (MMSE) were administered. Results: A total of 233 patients (112 with asthma and 121 with COPD; mean age 57.9 ± 11.9 years) were included in the study. Patients with COPD or asthma had a low QoL as estimated by the SGRQ (mean ± SD: 27.5 ± 12.9 and 25.1 ± 10.2 for asthma and COPD, respectively). Asthma exacerbations, COPD exacerbations or SP requiring hospitalization were associated with lower SGRQ scores over the three-year observation period (41.5 ± 11.7, 57.9 ± 14.3 and 65.3 ± 11.4, respectively). The mean MMSE score significantly decreased after an asthma exacerbation compared to the baseline (29.9 ± 2.1 versus 27.2 ± 3.1; p < 0.05). The mean MMSE score decreased after COPD exacerbations (28.5 ± 0.9 versus 26.9 ± 1.2; p < 0.05) and after COPD with an SP event (28.8 ± 1.2 versus 24.1 ± 2.2; p < 0.05). Conclusion: Low QoL and mental impairment were observed in patients with asthma and COPD. In addition, the QoL significantly decreased following hospitalizations due to exacerbations or SP.